Pengembangan Infrastruktur Pelabuhan Panjang Sebagai Pelabuhan Cargo Bertaraf Internasional - Rachmadi, Adi (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Infrastructure development in Indonesia continued to show progress, including the development of the port as a place which is an integrated system consisting of transport in the waters, port, safety and security, and environmental protection in maritime. Lampung province that has the port will control that is essential for the regions surrounding potential in improving the economy, especially industry and trade both nationally and internationally. The purpose of this study was to assess the Port of Panjang infrastructure development as an international cargo port. Therefore, researchers using the theory to fill positivistic approach and examples of best practice to fill rationalistic. Best practice is used is the Port of TanjungPriok, Jakarta, and Port of Busan, South Korea as a cornerstone of researchers to conduct research. The research character is a descriptive. Methods of data collection is done by direct observation to the test site and interview techniques combined with a list of questions to the government and service users. The results showed Port of Panjang Infrastructure meet the minimum requirements of international cargo ports established by the IMO, the Port of Panjang must add infrastructure and supporting facilities. Water facilities, ports should be developed, among others, relocation is docked tug boat, pilot boat and service boat, while the infrastructure to be developed is the yard, office building (banking) and postal telecommunications, reactivation of the railway to transport coal, and gangway to lane expressway passenger sea.Â